Attitude Toward Online English Learning, Satisfaction On The Use Of Virtual English Learning Environment, And English Performance Of Junior High Schoolstudents Of Pedro T. Mendiola Sr. Memorial National High School - Ruth G. Hablo, Mat, Diana; D. Gorospe, Edd, Joanne (CV. Inara, 2022)
This study aimed to find the relationship between and among the students’ attitude toward online English learning, satisfaction on the use of virtual English learning environment, and English performance. Descriptive-correlational and descriptive-predictive research designs were used in this study. A total of 150 junior high school students of Pedro T. Mendiola Sr. Memorial National High School enrolled in online classes of School Year 2020-2021 were the respondents of the study. The respondents were selected through stratified random sampling. The data were gathered and analyzedusing a closed questionnaire with 5-point Likert Scale. Results of the study revealed that the students have a neutral attitude towards online English learning, and also neutral in terms of interest in computer and adoption of online learning, effectiveness of online learning, and ease-ness in using online learning. The students have high level of satisfaction on the use of virtual English learning environment, in terms of learner interface, learning community, content, and usefulness. The students have a high performance in English. The students’ attitude towards online English learning is significantly related to their level of satisfaction on the use of virtual learning environment. The students’ attitude towards online English learning has significant relationship with their English performance. The students’ satisfaction on the use of virtual English learning environment and their English performance are significantly related. The factors of attitude towards OEL that predict the satisfaction on the use of VELE of the students are effectiveness of online learning and ease-ness in using online learning. None of the factors of attitude towards online English learning best predicts the English performance of the students. None of the factors of satisfaction on the use of virtual learning environment best predicts the English performance of the students. With the findings of the study, it is concluded that the students’ attitude towards online English learning and their